Fungal Gene-Encoded Peptidase Inhibitors - Bauerova, V.; Pichova, I.; Hruskova-Heidingsfeldova, O. (Current Medicinal Chemistry, 2013)
Peptidases can be inhibited by natural or synthetic small-molecule compounds, or by gene-encoded, proteinaceous inhibitors. Small-molecule peptidase inhibitors have been in the spotlight of researchers and pharmaceutical companies for many years. The studies concerning gene-encoded inhibitors are less frequent. The last decade has seen a boom of fungal genomics followed by extensive bioinformatic analyses focused particularly on those species that can cause infections in humans, animals or crops. Many sequences of putative inhibitors have been identified on the basis of homology with gene-encoded peptidase inhibitors of Saccharomyces cerevisiae, mammals or other organisms. However, characterization of the respective proteins is often missing. Gene-encoding peptidase inhibitors are rather diverse in size, mode of action, type of the target peptidase and localization. While some of the inhibitors are secreted to extracellular space and participate in host-pathogen interactions, others act intracellularly and their precise role in fungal physiology is not fully understood. However, most of the gene-encoded peptidase inhibitors are rather selective and efficient, and may be an inspiration for future directions of antimycotic research.
Keywords: AFUEI